N‐glycolylneuraminic acid knockout reduces erythrocyte sequestration and thromboxane elaboration in an ex vivo pig‐to‐human xenoperfusion model. (22nd September 2017) - Cimeno, Arielle; Hassanein, Wessam; French, Beth M.; Powell, Jessica M.; Burdorf, Lars; Goloubeva, Olga; Cheng, Xiangfei; Parsell, Dawn M.; Ramsoondar, Jagdeece; Kuravi, Kasinath; Vaught, Todd; Uluer, Mehmet C.; et al.
Abstract: Background: Wild‐type pigs express several carbohydrate moieties on their cell surfaces that differ from those expressed by humans. This difference in profile leads to pig tissue cell recognition of human blood cells causing sequestration, in addition to antibody‐mediated xenograft injury. One such carbohydrate is N‐glycolylneuraminic acid (Neu5Gc), a sialic acid molecule synthesized in pigs but not in humans. Here, we evaluate livers with and without Neu5Gc in an ex vivo liver xeno perfusion model. Methods: Livers from pigs with an α1, 3‐galactosyl transferase gene knockout (GalTKO) and transgenic for human membrane cofactor (hCD46) with (n = 5) or without (n = 7) an additional Neu5Gc gene knock out (Neu5GcKO) were perfused ex vivo with heparinized whole human blood. A drug regimen consisting of a histamine inhibitor, thromboxane synthase inhibitor, and a murine anti‐human GPIb‐blocking antibody fragment was given to half of the experiments in each group. Results: Liver function tests (AST and ALT) were not significantly different between livers with and without the Neu5GcKO. GalTKO.hCD46.Neu5GcKO livers had less erythrocyte sequestration as evidenced by a higher mean hematocrit over time compared to GalTKO.hCD46 livers ( P  = .0003). The addition of Neu5GcKO did not ameliorate profound thrombocytopenia seen within the first 15 minutes of perfusion. TXB2 was significantly less with the added drug regimen ( P  = .006) or the presence of Neu5GcKO ( P  = .017). Conclusions: The lack of Neu5Gc expression attenuated erythrocyte loss but did not prevent profound early onset thrombocytopenia or platelet activation, although TXB2 levels were decreased in the presence of Neu5GcKO.